Wisent in Ukrainian culture: a difficult trail and uncertain finale (European Bison Conservation Newsletter, 2012)
Apparently, in ancient Ruthenia, the European bison (zubr) was not distinguished from another native large bovine – the aurochs (tur), because both animals were perceived as impersonation of wild power. A victory over any of them aroused common respect. The name “zubr” is not used in our ancient sources. However, the word “tur” is often found. For example,it is used 5 times, mainly as an addition to prince names, in “The Tale of Igor’s Campaign” – a monument of ancient Ruthenian literature of the XII century. Big bull that was called tur is also mentioned in another famous piece of literature of the XII century – “The lesson of Volodymyr Monomach”. Prof. M. Sharleman – a great expert on ancient Ruthenian nature – pointed out that this name was used then for both: the true tur (Bos primegenius) and zubr (Bison bonasus). The scientist noted that even in the beginning of XX century, big bulls were called “turs” in some regions of Ukraine. It is believed that real tur became extinct in Ukraine as late as in the XVII century. However, Sharleman (1997) considered that this species vanished from the territory of Ruthenia relatively early. This is corroborated by the records indicating that by the turn of the XVI-XVII centuriesturs occurred only in Jaktorowska Forest, located 60 km to the west from Warsaw. Thus, the name of extinct turs could be transferred upon European bison, which, according to Sharleman’s opinion, lived at the territory of Ukraine even in the XVI century, or in accordance with other data – until the beginning of the XIX century. Therefore, the so-called “steppe buffalos”, which lived closer to the border with Moscow state and were mentioned by Boplan in his “Description of Ukraine” in 1660, most likely should be attributed to European bison. In the XVI–XVII centuries, “zubr” was descripted as wild, fierce animal. Preserved evidence testifies that within present territory of Ukraine, they lived at the border with Russia and near Zaporizhzhya. Not later than in the beginning of the XIX century E.bison became completely extinct from the territory of Ukraine. The old-time memories about zubr remain only in topographic names of Lviv (the Zubra river, the village of Zubritsya), Chernivtsi (the Zubrovytsya river and Zubrinets hollow) and Khmelnytski (the village of Zubrovka in Kamyanets-Podilski district) regions.For the first time European bison was reintroducted to Ukraine in the beginning of the XX century as the animal for elite hunting. The first efforts to return this species back to Ukraine were made when animals were brought from Białowieża to the hunting park of Jo´ zef Potocki “Pilawin” (nowadays – Nowograd-Wolynski district of Zhytomyr region). In the winter of 1913 pure blood animals from Białowiez˙a were brought to the Crimea, to a hunting ground belonging to the tsar (at present Crimean nature reserve). Since the purpose of bringing this animal there was not its protection but hunting, the whole initiative ended up in 1908, when a monument was raised there to commemorate the last E.bison shot by a foreign hunter.However, since the second reintroduction of the species to the territory of Ukraine in the beginning of the 60-ies of the XX century, “zubr” is perceived as the symbol of nature protection. This image is widely represented in all media and other materials devoted to nature protection. A monument of E.bison, probably the largest in Europe, was built near the entrance of Kyiv Zoo. Unfortunately in the period between 1990–2000, European bison again became associated with the fierce power, so the possession of its trophy was regarded as prestigious. This stimulated poaching both by common people and elites, and caused a dramatic decrease of Ukrainian population. That is why one of the most important goals today is to change publicopinion about zubr. Today Ukrainian NGOs and scientific institutions try to change the image of European bison from a game animal to a treasure of wild nature, and a relic of Kyiv’ Ruthenia.
Keywords: wisent; Ruthenia; Ukraine; history